Penyuluhan Nutrisi pada Ibu Hamil untuk Mencegah dan Menanggulangi Anemia Gizi Besi melalui Komunikasi Interpersonal - Agustina Agustina; Retno Dyah Kusumastuti; Putri Permatasari (Jurnal Pengabdian Pada Masyarakat, 2020)
NUTRITION COUNSELING TO PREGNANT WOMEN TO PREVENT AND MEDICATE IRON ANEMIA THROUGH INTERPERSONAL COMMUNICATION. Iron deficiency anemia pregnant women, due to iron deficiency in the body, results in miscarriage, premature birth, low birth weight, susceptible to infection, bleeding during childbirth which resulting in death and intelligence disorders in children. One of the causes of the high incidence of anemia is lack of knowledge of pregnant women about iron defecency anemia, nutritional sources of iron, higher iron nutrition needs during pregnancy, reluctant to consume iron tablets. The aim of the service is to increase the understanding of pregnant women about the nutrition of iron sources, iron needs, iron tablets and factors that facilitate and inhibit iron absorption in the body. The method used is to provide counseling to anemic pregnant women, through interpersonal communication. The results of the activities before counseling obtained knowledge of Iron deficiency anemia and knowledge of nutrient sources of iron, knowledge of iron tablets in the low category. After being given interpersonal counseling, participants 'knowledge increased to a good category, marked by an increase in participants' hemoglobin after 20 days after counseling. Conclusion Interpersonal counseling methods is one way to overcome and prevent iron nutritional anemia. Suggestions for increasing knowledge and changing behavior will be more effectively conveyed through interpersonal communication.